Implementing Islamic Montessori Learning to Foster Islamic Religious Values in Early Childhood Education: A Case Study - Tiara Margareta Sukma Azis; Fikri Nazarullail; Dewi Mayangsari; Dinda Rizki Tiara; Angga Fitriyono (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: The cultivation of Islamic religious values in early childhood is essential for developing children’s moral character, spiritual awareness, and social behavior. However, learning practices in many early childhood education settings still rely heavily on rote memorization and teacher-centered instruction, resulting in limited opportunities for children to internalize Islamic values through meaningful daily experiences. The Islamic Montessori approach has emerged as an alternative pedagogical model that integrates Montessori child-centered principles with Islamic teachings in structured and practical learning activities. This approach is considered capable of fostering children’s independence, responsibility, and religious character in a more natural and enjoyable manner. Aims and scope of paper: This study aimed to explore the implementation of Islamic Montessori learning in cultivating Islamic religious values among children aged 4–5 years at TKIT Al-Irsyad Al-Islamiyyah Pamekasan, Indonesia. Methods: This study employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving the principal, teachers, educational staff, and parents. The primary informants were the classroom teacher and the principal, while assistant teachers and parents served as supporting informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to identify patterns in the implementation of Islamic Montessori learning practices. Results: The findings revealed that the implementation of Islamic Montessori learning at TKIT Al-Irsyad Al-Islamiyyah was conducted systematically through opening activities, core learning activities, and comprehensive evaluations. The core learning process was implemented across several Montessori learning areas, including Practical Life, Sensorial, Language, and Islamic Studies, all of which were integrated with Islamic values related to faith, worship, and moral behavior. The study demonstrated that Islamic Montessori learning effectively facilitated the internalization of Islamic religious values through meaningful and child-centered activities. In addition, the approach contributed to the development of children’s independence, discipline, responsibility, and positive Islamic character from an early age. Contribution: This study contributes to the growing literature on Islamic early childhood education by providing empirical evidence regarding the integration of Montessori pedagogy and Islamic values in preschool learning environments.